When males are more inclined to stay at home :Insights into the partial migration of a pelagic seabird provided by geolocators and isotopes - Perez, Cristóbal (2016)
Partial migration has never been studied in pelagic seabirds, but investigating old unresolved questions in new contexts can provide useful fresh insights. We used geolocators and stable isotopes to investigate this phenomenon in a migratory pelagic seabird, the Cory’s shearwater (Calonectris diomedea). Although most birds migrated to the southern hemisphere, 8.1% of studied birds (N = 172) remained close to the breeding colony (Selvagem Grande, Madeira, Portugal), foraging within the Canary current. Almost all resident birds were males, while age or body size did not predict migratory status. Despite displaying a high repeatability (R = 0.72) in the choice of wintering area, residency was not a fixed strategy and individuals could switch between migrating and staying in the Canary current in different years. The predictions resulting from the “body size” and the “social dominance” hypotheses, in which larger individuals or dominant individuals, respectively, remain closer to the breeding areas, were not supported by our data. Resident males were able to occupy the nesting burrows much earlier than migratory males and arrival time in this species is known to affect the probability of engaging in a reproductive attempt. The selective pressure to arrive early at the colony is therefore the most likely explanation for the maintenance of this partial migration system.